Evaluation of Intralymphatic Immunotherapy in Allergic Rhinitis Patients: A Systematic Review and Meta-analysis - Sijie Jiang; Shaobing Xie; Qingping Tang; Hua Zhang; Zhihai Xie; Junyi Zhang; Weihong Jiang (Mediators of Inflammation)
Background. Intralymphatic immunotherapy (ILIT) is short-course administration of allergen-specific immunotherapy (AIT). This study is aimed at assessing the clinical efficacy and safety of ILIT in patients with allergic rhinitis (AR). Methods. MEDLINE, PUBMED, and Cochrane Library were used to conduct electronic searches for clinical trials comparing ILIT and placebo in patients with AR. The final search took place on August 24, 2022. Cochrane Handbook for Systematic Reviews of Interventions was used to assess the risk of bias in the included studies. The outcomes included combined symptom and medication scores (CSMS), visual analog scale (VAS), allergic rhinoconjunctivitis quality of life (RQLQ), Skin-prick test (SPT), and adverse events (AEs). Data were synthesized as mean difference (MD)/standard mean difference (SMD) or risk difference (RD) and 95% confidence interval (CI). Results. Thirteen studies (454 participants) were included in this study. The ILIT group had better clinical improvement on the CSMS (random effects model, SMD-0.85, 95% CI [-1.58, -0.11], P=0.02) and RQLQ (fixed-effects model, MD-0.42, 95% CI [0.69, 0.15], P=0.003) than the placebo group. The booster injection was beneficial for CSMS (P<0.0001), and the 4-week injection interval was superior to the 2-week injection period for improving VAS (P<0.0001). Local swelling or erythema was the main AE following injection (random effects model, RD 0.16, 95% CI [0.05, 0.27], P=0.005). Discussion. For individuals with AR, ILIT is safe and effective. ILIT alleviates clinical symptoms and reduces pharmaceutical consumption without causing severe AEs. However, the validity of this study is compromised by the substantial heterogeneity and risk of bias in the included researches. RegistrationCRD42022355329.